DNA methylation profiles distinguish different subtypes of gastroenteropancreatic neuroendocrine tumors. (December 2015) - How-Kit, Alexandre; Dejeux, Emelyne; Dousset, Bertrand; Renault, Victor; Baudry, Marion; Terris, Benoit; Tost, Jörg
Aim: Most studies have considered gastroenteropancreatic neuroendocrine tumors (GEP-NETs) as a homogenous group of samples or distinguish only gastrointestinal from pancreatic endocrine tumors. This article investigates if DNA methylation patterns could distinguish subtypes of GEP-NETs.Materials & methods: The DNA methylation level of 807 cancer-related genes was investigated in insulinomas, gastrinomas, non-functioning pancreatic endocrine tumors and small intestine endocrine tumors.Results: DNA methylation patterns were found to be tumor type specific for each of the pancreatic tumor subtypes and identified two distinct methylation-based groups in small intestine endocrine tumors. Differences of DNA methylation levels were validated by pyrosequencing for 20 candidate genes and correlated with differences at the transcriptional level for four candidate genes.Conclusion: The heterogeneity of DNA methylation patterns in the different subtypes of gastroenteropancreatic neuroendocrine tumors suggests different underlying pathways and, therefore, these tumors should be considered as distinct entities in molecular and clinical studies.